Integrative inclusive problem based fiqh learning for contextual understanding and epistemic engagement - Musonif, Irfan; Aisyah Puan Maharani; Mahin Anas Ramadona; Saifudin, Saifudin; Rohman Hakim (ATTARBIYAH: Journal of Islamic Culture and Education, 2026)
The dominance of text-centered and normative pedagogies in Islamic religious education often limits students' ability to engage critically, contextually, and inclusively with fiqh learning. This study examines how an integrative–inclusive problem-based learning model can transform fiqh learning toward more contextual and interpretive engagement. Using a qualitative case study design, the research was conducted in an eleventh-grade classroom at a Madrasah Aliyah in Indonesia from January to February 2026, involving one teacher and 32 students. Data were collected through classroom observations, semi-structured interviews, and document analysis, then analyzed using reflexive thematic analysis. The findings reveal that fiqh learning exists within a transitional space where normative transmission coexists with emerging contextual approaches. Problem-based learning increases student engagement and supports contextual reasoning, although its implementation remains situational rather than systematically embedded. The study also identifies a gap between procedural and epistemic inclusion, indicating that classroom participation does not necessarily ensure equitable knowledge construction. Furthermore, epistemic tension between normative legalism and contextual meaning-making emerges as a productive aspect of learning. This study contributes to Islamic education discourse by introducing the concepts of closed epistemic structures, situated pedagogical innovation, and productive epistemic friction as frameworks for reflective and context-responsive fiqh learning.